TINJAUAN TERHADAP KUALITAS PELAYANAN DI RESTORAN DAPOER KIM KARAWANG - Iskandar, Antonius; Kristianto, Aloysius (Akademi Pariwisata NHI Bandung, 2023)
This study aimed to identify and analyzed the level of Service Quality At Dapoer Kim Restaurant Karawang. The results of this research are as follows: 1) the level of implementation of the tangible aspect has an average score of 919.00; 2) The level of implementation of the reliability aspect has an average score of 797.00; 3) The level of responsiveness aspect has an average score of 631.00. 4) The level of implementation of the assurance aspect has an average score of 754. 5) The level of implementation of the empathy aspect has an average score of 990. The overall results of the analysis at level 1) tangible are in the Good category; 2) reliability is in the sufficient category; 3) responsiveness is in the low category; 4) assurance is in the sufficient category; 5) empathy is in the good category. The conclusion of this research is that the quality of employee service to Dapoer Kim Karawang restaurant guests is less than optimal